Nursing Care for Decubitus Prevention using Range of Motion (ROM) in Patients with Stroke at Ikedaen Byoing Hospital Japan - Susianti, Yayuk; Jati, Riani Pradara (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Tissue damage due to pressure on soft tissue, decubitus often occurs in patients who are bedridden for long periods of time. One way to prevent pressure ulcers is by massaging using moisturizer such as pure coconut oil and doing Range Of Motion (ROM). This scientific research aims to determine the effectiveness of bed shifting or Range Of Motion (ROM) as an effort to prevent pressure ulcers. The ROM method is carried out 3 days in a row every 2 hours in the morning, afternoon, and evening. After implementing ROM (Range Of Motion) result obtained in these patients for 3 days periodically showed a reduction in complaints of pain when lying in bed. The ROM (Range Of Motion) method has been proven to be effective in preventing pressure ulcers in stroke patient who are bedridden for a long time. The ROM (Range Of Motion) method is very effective in helping prevent decubitus in bed rest patients such as stroke.